Mixed-ligand copper(II) complexes activate aryl hydrocarbon receptor AhR and induce CYP1A genes expression in human hepatocytes and human cell lines - Kubešová, Kateřina; Dořičáková, Aneta; Trávníček, Zdeněk; Dvořák, Zdeněk (Toxicology letters, 2016)
The effects of four copper(II) mixed-ligand complexes [Cu(qui1)(L)]NO3·H2O (1-3) and [Cu(qui2)(phen)]NO3 (4), where qui1=2-phenyl-3-hydroxy-4(1H)-quinolinone, Hqui2=2-(4-amino-3,5-dichlorophenyl)-N-propyl-3-hydroxy-4(1H)-quinolinone-7-carboxamide, L=1,10-phenanthroline (phen) (1), 5-methyl-1,10-phenanthroline (mphen) (2), bathophenanthroline (bphen) (3), on transcriptional activities of steroid receptors, nuclear receptors and xenoreceptors have been studied. The complexes (1-4) did not influence basal or ligand-inducible activities of glucocorticoid receptor, androgen receptor, thyroid receptor, pregnane X receptor and vitamin D receptor, as revealed by gene reporter assays. The complexes 1 and 2 dose-dependently induced luciferase activity in stable gene reporter AZ-AhR cell line, and this induction was reverted by resveratrol, indicating involvement of aryl hydrocarbon receptor (AhR) in the process. The complexes 1, 2 and 3 induced CYP1A1 mRNA in LS180 cells and CYP1A1/CYP1A2 in human hepatocytes through AhR. Electrophoretic mobility shift assay EMSA showed that the complexes 1 and 2 transformed AhR in its DNA-binding form. Collectively, we demonstrate that the complexes 1 and 2 activate AhR and induce AhR-dependent genes in human hepatocytes and cancer cell lines. In conclusion, the data presented here might be of toxicological importance, regarding the multiple roles of AhR in human physiology and pathophysiology.
Keywords: hepatocyty; Basic Helix-Loop-Helix Transcription Factors; dospělí; primární buněčná kultura; vztah mezi dávkou a účinkem léčiva; Nitrates; Copper(II) complexes; Adult; MFC-7 buňky; transkripční faktory bHLH; transfekce; Transcription, Genetic; Transfection; lidé; receptory aromatických uhlovodíků; MCF-7 Cells; messenger RNA; Cytochrome P450; Phenanthrolines; měď; Cytochrome P-450 CYP1A1; Hepatocytes; Copper; Ligands; RNA, Messenger; genetická transkripce; Dose-Response Relationship, Drug; Receptors, Aryl Hydrocarbon; Cytochrome P-450 CYP1A2; Male; Xenobiotics; Aged; Human hepatocytes; cytochrom P-450 CYP1A1; aktivace transkripce; Primary Cell Culture; Enzyme Induction; enzymová indukce; Nuclear receptors; lidé středního věku; fenantroliny; senioři; cytochrom P-450 CYP1A2; mužské pohlaví; dusičnany; Middle Aged; Transcriptional Activation; ligandy; Humans